A comparison of Inconel 718 obtained with three L-PBF production systems in terms of process parameters, as-built surface quality, and fatigue performance. (September 2022) - Uriati, Federico; Nicoletto, Gianni
Highlights: Fatigue strength differences are observed in as-built IN 718 specimens manufactured with different AM production equipment. Sets of miniature specimens differently oriented were fabricated according to optimized process parameters and heat-treatment. The fatigue behavior of IN718 with as-built surfaces depends significantly on surface orientation and process parameters. The link between final part properties and the entire AM production process is highlighted. Abstract: Industry-grade Powder Bed Fusion (PBF) systems operated according to qualified processing parameters and procedures are expected to manufacture metal parts of highly complex geometry. However, variation of the mechanical properties of components obtained with different qualified production equipment for the same powder and production workflow has been observed. This dependence of the final L-PBF part performance on a multitude of factors is of concern for the application engineer. The present work aims to shed light on the role of process equipment on fatigue performance and focuses on Inconel 718 alloy processed by a qualified service provider using three industry-grade L-PBF systems working with different layer thicknesses. A novel method based on the use of miniature specimens is being used; this innovative approach allows to efficiently investigate fatigue behavior with less material consumption compared to standard methods and favoured by the small dimension, the coupons can be freely positioned inside the chamber to investigate different built direction and their consequent effect on mechanical properties. Sets of miniature specimens oriented along different directions with respect to build direction were fabricated with each system according to its optimized process parameters, heat-treated according to the same dual-step thermal cycle and characterized in terms of hardness, surface roughness, and finally tested in the high cycle fatigue regime with the surfaces in the as-built condition. The directional specimens exhibits degrees of anisotropic fatigue behavior in dependence of the production equipment. The present test results define a scatter in fatigue performance that can support the design of L-PBF Inconel 718 parts.